ENVIRONMENTAL IMPACTS ON INADEQUATE DESTINATION URBAN SOLID WASTE IN THE CITY OF IPAMERI-GO: A CASE STUDY - Silva, Maria Cleonice da Conceição; Pelá, Adilson; Barretos, Flávia Risse de Mattos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Developing countries have big social and environmental. In Brazil, inequality and environmental problems are clearly visible, especially in the suburbs of the cities, making it very difficult to remedy or minimize solid waste. The objective of this work is to study the situation of inadequate disposal of solid waste by residents Ipameri-GO, in the current context of the municipality and, if possible, observe the contempt with which they are being treated solid waste that they are deposited, without any treatment in various locations around the city, such as vacant lots and roadsides, which shows that the city’s waste Ipameri have no way of integrated management by the municipal administrators. Still, this problem has triggered pollution problems in various parts of the city, such as visual pollution and environmental pollution, which leaves one aspect of indignation for environmentalists city. However, public managers have a very important role in relation to waste, and to seek a solution for the integrated management of solid waste through technologies and sustainable solutions that can sensitize the entire community of the importance of proper disposal of solid waste.